Luteinizing Hormone Facilitates Antral Follicular Maturation and Survival via Thecal Paracrine Signaling in Cattle - Hattori, Katsushige; Orisaka, Makoto; Fukuda, Shin; Tajima, Kimihisa; Yamazaki, Yukiko; Mizutani, Tetsuya; Yoshida, Yoshio (Endocrinology (Philadelphia), 2018)
Abstract LH supplementation in assisted reproductive technology cycles improves the ongoing pregnancy rate in women with poor ovarian response (POR). However, our knowledge of the precise role of LH during the follicular phase of the menstrual cycle is incomplete. To explore the role of LH in the maturation of small antral follicles, we used an in vitro two-cell system that involved coculturing bovine granulosa cells (GCs) and theca cells (TCs) on a collagen membrane. Treatment of TCs with LH stimulated androgen production in TCs by inducing the expression of androgenic factors, subsequently increasing estrogen biosynthesis in GCs by providing androgen substrates, and inducing aromatase expression. LH stimulation of TCs induced functional LH receptor expression in GCs, a response modulated by the synthesis and action of estrogen. In the presence of TCs, LH stimulation of TCs and FSH stimulation of GCs increased the expression of IGF-1, IGF-2, and IGF-1 receptor in GCs. LH-induced expression of thecal IGF-1 protected GCs from apoptosis and promoted GC survival. Furthermore, LH stimulation of TCs increased FSH sensitivity in GCs. Thus, the LH–TC axis may be involved in the acquisition of LH dependence and the survival of small antral follicles by upregulating androgen/estrogen biosynthesis and activating the IGF system. The use of LH supplementation in ovarian stimulation may increase gonadotropin sensitivity in small antral follicles and promote follicular growth and survival by suppressing GC apoptosis and follicular atresia, resulting in multiple follicular development, even in patients with POR. The LH–TC axis facilitates ovarian follicle maturation and survival by upregulating androgen/estrogen biosynthesis and activating the IGF system in small antral follicles.